Regulation of ROS signal transduction by NADPH oxidase 4 localization - Chen, Kai; Kirber, Michael T; Xiao, Hui; Yang, Yu; Keaney, Jr, John F (The Journal of cell biology, 2008)
Reactive oxygen species (ROS) function as intracellular signaling molecules in a diverse range of biological processes. However, it is unclear how freely diffusible ROS dictate specific cellular responses. In this study, we demonstrate that nicotinamide adenine dinucleotide phosphate reduced oxidase 4 (Nox4), a major Nox isoform expressed in nonphagocytic cells, including vascular endothelium, is localized to the endoplasmic reticulum (ER). ER localization of Nox4 is critical for the regulation of protein tyrosine phosphatase (PTP) 1B, also an ER resident, through redox-mediated signaling. Nox4-mediated oxidation and inactivation of PTP1B in the ER serves as a regulatory switch for epidermal growth factor (EGF) receptor trafficking and specifically acts to terminate EGF signaling. Consistent with this notion, PTP1B oxidation could also be modulated by ER targeting of antioxidant enzymes but not their untargeted counterparts. These data indicate that the specificity of intracellular ROS-mediated signal transduction may be modulated by the localization of Nox isoforms within specific subcellular compartments.